The Effect of Temperature on the Stability of PCSK-9 Monoclonal Antibody: An Experimental Study - Kongmalai, Tanawan (J Endocr Soc, 2021)
Background: PCSK9 monoclonal antibody lowers plasma PCSK9 and LDL-cholesterol levels. The manufacturers recommend drug storage at 2–8°C, and not above 25°C. This study aimed to investigate drug stability at various temperatures that this drug could be exposed to during medication handling and transportation in tropical countries. Methods: Alirocumab and evolocumab were tested in 3 study conditions: room temperature (RT), cooler device with cold pack, and freeze-thaw for 9 and 18 hours. Heated drugs were used as negative control. Free plasma PCSK9 levels from 9 hyperlipidemia subjects were measured with ELISA. Results: Average subject age was 49.2±18.4 years. Percent PCSK9 inhibition significantly declined in heated drugs compared to baseline. Average RT during the study period was 30.4°C. Change in percent PCSK9 inhibition of PCSK9 mAb at RT from baseline was -5.8±4.4 (p=0.005) and -11.0±8.9% (p=0.006) for alirocumab at 9 hours and 18 hours, and -9.7±11.8% (p=0.04) and -15.1±14.3% (p=0.01) for evolocumab at 9 and 18 hours, respectively. In contrast, there were no significant changes in percent PCSK9 inhibition from baseline when PCSK9 mAb was stored in a cooler. In freeze-thaw condition, changes in percent PCSK9 inhibition from baseline to 9 and 18 hours were -5.2±2.9% (p=0.001) and -2.6±4.9% (p=0.16) for alirocumab, and -1.8±4.2% (p=0.24) and 0.4±6.1% (p=0.83) for evolocumab. Conclusion: Proper drug storage according to manufacturer’s recommendation is essential. Drug storage at RT in tropical climate for longer than 9 hours significantly decreased drug efficacy; however, storage in a cooler device with cold pack for up to 18 hours is safe.